Pengaruh Reputasi terhadap Legitimasi di Perguruan Tinggi Indonesia - Julita, Intan; Baihaqi, Baihaqi (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This research aims to examine the influence of reputation on legitimacy. The population in this study were Senior Lecturers in Accounting Study Programs in all Indonesian Universities. Sampling in this research used the technique of distributing questionnaires directly to Senior Accounting Lecturers in the form of a Google form. Data collection used a sample of 42 Senior Accounting Lecturers from 37 Universities in Indonesia using purposive sampling. This research considers pragmatic, moral, and cognitive types of legitimacy, and analyzes reputation in relation to performance, innovation, social responsibility, service, governance, and workplace climate. According to lecturers, a university's reputation has a positive influence on its legitimacy. Data processing and testing uses structural modeling with the SmartPLS version 3 system.